Positive Allosteric Modulation of Cannabinoid Receptor Type 1 Suppresses Pathological Pain Without Producing Tolerance or Dependence - Slivicki, Richard A.; Xu, Zhili; Kulkarni, Pushkar M.; Pertwee, Roger G.; Mackie, Ken; Thakur, Ganesh A.; Hohmann, Andrea G. (Biological psychiatry (1969), 2018)
Activation of cannabinoid CB1 receptors suppresses pathological pain but also produces unwanted central side effects. We hypothesized that a positive allosteric modulator of CB1 signaling would suppress inflammatory and neuropathic pain without producing cannabimimetic effects or physical dependence. We also asked whether a CB1 positive allosteric modulator would synergize with inhibitors of endocannabinoid deactivation and/or an orthosteric cannabinoid agonist. GAT211, a novel CB1 positive allosteric modulator, was evaluated for antinociceptive efficacy and tolerance in models of neuropathic and/or inflammatory pain. Cardinal signs of direct CB1-receptor activation were evaluated together with the propensity to induce reward or aversion and physical dependence. Comparisons were made with inhibitors of endocannabinoid deactivation (JZL184, URB597) or an orthosteric cannabinoid agonist (WIN55,212-2). All studies used 4 to 11 subjects per group. GAT211 suppressed allodynia induced by complete Freund’s adjuvant and the chemotherapeutic agent paclitaxel in wild-type but not CB1 knockout mice. GAT211 did not impede paclitaxel-induced tumor cell line toxicity. GAT211 did not produce cardinal signs of direct CB1-receptor activation in the presence or absence of pathological pain. GAT211 produced synergistic antiallodynic effects with fatty acid amide hydrolase and monoacylglycerol lipase inhibitors in paclitaxel-treated mice. Therapeutic efficacy was preserved over 19 days of chronic dosing with GAT211, but it was not preserved with the monoacylglycerol lipase inhibitor JZL184. The CB1 antagonist rimonabant precipitated withdrawal in mice treated chronically with WIN55,212-2 but not in mice treated with GAT211. GAT211 did not induce conditioned place preference or aversion. Positive allosteric modulation of CB1-receptor signaling shows promise as a safe and effective analgesic strategy that lacks tolerance, dependence, and abuse liability.